The Japanese plasma cell dyscrasia syndrome: case report and theory of pathogenesis. Issue 686 (December 1982) - Tobin, Martin J.; FitzGerald, Muiris X.
Abstract : A 54-year-old man developed pigmentation, clubbing, weight loss, oedema, hepatomegaly, lymphadenopathy, cold intolerance, hypotonia and hyporeflexia. Dominant laboratory findings were increased marrow plasma cells with IgA lambda paraproteinaemia, hypothyroidism, hyperprolactinaemia, hyperoestrogenaemia and biopsy-proven peripheral neuropathy. The clinical features and dramatic response to corticosteroids are consistent with the syndrome of plasma cell dyscrasia, polyneuropathy and endocrinopathy found predominantly in Japan. In our patient, immunofluorescence of neural tissues revealed paraprotein deposition. Although the pathogenesis is unknown, these multisystemic features may result from antibody activity or tissue deposition of paraprotein. Furthermore, the endocrinopathy may be localized at the hypothalamic level.